USING MIND MAPPING TO IMPROVE STUDENTS’ SPEAKING SKILL AT SECONDARY SCHOOL - Nurfadila Hasani, (Jurnal Cakrawala Ilmiah, 2024)
This study examines the impact of the mind mapping technique to improve students' speaking skills at an Indonesian secondary school. This study employed an experimental design, involving a pre-test and post-test. A treatment was given between the two tests, following the pre-test. Data were analyzed using descriptive analysis by comparing the pre-test and post-test results to determine whether students' speaking abilities improved after the treatment. Through a treatment involving mind mapping, students showed significant improvements in speaking accuracy, fluency, and comprehensibility. The score of pre-test and post-test reveal gains in accuracy (1.2 points), fluency (1.37 points), and comprehensibility (0.83 points). The statistical analysis also demonstrated a significant t-test value of 12.59, further validating the effectiveness of mind mapping. Students expressed increased enthusiasm and confidence in speaking activities, highlighting mind mapping's role in fostering better communication. This research suggests that mind mapping can be an effective tool in English language education, with potential for broader application across different learning contexts.